Efficient Production of Broad-Spectrum Antimicrobials by Paenibacillus polymyxa OSY–EC Using Acid Whey-Based Medium and Novel Antimicrobial Concentration Approach - Abdelhamid, Ahmed G.; Campbell, Emily P.; Hawkins, Zach; Yousef, Ahmed E. (Frontiers in Bioengineering and Biotechnology, 2022)
Production of some antimicrobial peptides by bacterial producers is a resource-intensive process, thus, using inexpensive growth media and simplifying antimicrobial extraction and down-stream processing are highly desirable. Acid whey, a dairy industry waste, is explored as a medium for production of broad–spectrum antimicrobials from selected bacteriocinogenic bacteria. Neutralized and yeast extract-supplemented acid whey was suitable for production of antimicrobials by four tested strains, but Paenibacillus polymyxa OSY–EC was the most prolific antimicrobial producer. Concentrating synthesized antimicrobials during culture incubation using beads of polymeric adsorbent resin, followed by solvent extraction and freeze-drying, resulted in antimicrobials-rich powder (AMRP). Under these conditions, P. polymyxa OSY–EC produced paenibacillin, polymyxin E, and fusaricidin, which are active against Gram-positive and Gram-negative bacteria and fungi, respectively. When media containing 2x and 4x minimum inhibitory concentrations of AMRP were inoculated with Listeria innocua and Escherichia coli, microbial populations decreased by ≥4–log CFU ml−1 in tryptic soy broth and ≥3.5–log CFU ml−1 in milk. The antimicrobial mechanism of action of AMRP solutions was attributed to the disruption of cytoplasmic membrane of indicator strains, L. innocua and E. coli. These findings exemplify promising strategies for valorization of acid whey via microbial bioreactions to yield potent antimicrobials.